Integrated Action Plan (IAP) for Selected Tribal and Backward Districts Glimpses of Some Projects Taken up under IAP Volume I - Planning Commission (Planning Commission, 2012)
The Integrated Action Plan (IAP) was approved by Government of India on 25.11.2010 for 60 Selected Tribal and Backward Districts in 9 States with a block grant of Rs. 25 crore and Rs. 30 crore for 2010- 11 and 2011-12 respectively, to be placed at the disposal of the Committee headed by the District Collector and consisting of the Superintendent of Police of the District and the District Forest Officer.
Planning Commission Government of India
Planning Commission Government of India